2018
DOI: 10.1021/acs.organomet.8b00289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protic Ligands in the Ir-Catalyzed Dehydrogenation of Formic Acid in Water

Abstract: New Ir-IPr complexes featuring a variety of chelate ligands, some of them featuring NH moieties, were synthesized. These complexes proved to be efficient catalysts for the dehydrogenation of formic acid in DMF and H 2 O. The dehydrogenation rates were dependent on the nature of the ligands that accompany IPr in the coordination sphere of the metal. In fact, complexes that contain protic ligands, namely, [Ir(8-aminoquinoline)(H) 2 (IPr)(PPhMe 2)]BF 4 and [Ir(CH 3 CN)(2-phenylimidazole)(H)(IPr)(PPhMe 2)]BF 4 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 65 publications
(156 reference statements)
0
28
0
Order By: Relevance
“…In the past decade, noble metal complexes with heterocyclic ligands, especially those bearing an N-H moiety, showed high efficiency in the DH of formic acid [24][25][26][27] or the hydrogenation of carbon dioxide. 28,29 In this context, a panel of manganese complexes was synthesized and tested for the DH of FA (Table 1).…”
Section: Investigations Of the Catalytic Performancementioning
confidence: 99%
“…In the past decade, noble metal complexes with heterocyclic ligands, especially those bearing an N-H moiety, showed high efficiency in the DH of formic acid [24][25][26][27] or the hydrogenation of carbon dioxide. 28,29 In this context, a panel of manganese complexes was synthesized and tested for the DH of FA (Table 1).…”
Section: Investigations Of the Catalytic Performancementioning
confidence: 99%
“…We demonstrated that the N‐H moieties of en and AmQ ligands play a crucial role in the initial activation of formic acid to facilitate the transfer hydrogenation of furfural to furfuryl alcohol, which eventually transformed to LA , . Very recently, Oro et al reported Ir‐NHC (NHC = N‐heterocyclic carbene) based complexes for formic acid dehydrogenation in DMF and H 2 O . Though these complexes exhibit only moderate activity in H 2 O, the initial TOF is highest (790 h –1 ) for the Ir‐NHC‐AmQ complex.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Very recently, Oro et al reported Ir-NHC (NHC = N-heterocyclic carbene) based complexes for formic acid dehydrogenation in DMF and H 2 O. [14] Though these complexes exhibit only moderate activity in H 2 O, the initial TOF is highest (790 h -1 ) for the Ir-NHC-AmQ complex. Moreover, a significant quenching of the catalytic activity of Ir-NHC complex was observed when AmQ was replaced with 8-(N,N-dimethylamino)quinoline (DMAmQ), suggesting the crucial role of NH moiety of AmQ in enhancing the catalytic activity for formic acid dehydrogenation in H 2 O. Envisioned by our previous observations, herein, we investigated in detail the dehydrogenation of formic acid over Ruarene complexes containing various nitrogen-donor chelating ligands and demonstrated the crucial role of these ligands on the formic acid dehydrogenation process.…”
Section: Introductionmentioning
confidence: 99%
“…In many scenarios, the reaction is performed in water, a benign and green solvent, but many other well‐working solvent systems are known to literature, including the direct dehydrogenation of neat FA . The continuous attempts to elucidate the mode of operation of various catalysts give detailed insight into the mechanistic processes during the reaction …”
Section: Introductionmentioning
confidence: 99%
“…Especially prolific are bidentate nitrogen donor ligands,[15b], [15f], phosphane containing structures, and pincer ligands. [13d], However, for a large‐scale application, first‐row transition metal catalysts are more attractive, for many reasons but mainly because they are cheap and abundant. The development of working iron catalysts is an essential step in this direction .…”
Section: Introductionmentioning
confidence: 99%